Effect of thinning and post-fire regeneration age on growth and reproductive traits of Pinus halepensis forests - Espelta J.M.; Verkaik I. (Proceedings of the international workshop MEDPINE 3: conservation, regeneration and restoration of Mediterranean pines and their ecosystems, 2007)
Post-fire regeneration of Pinus halepensis forests usually results in high density stands, where thinning is recommended to prevent the occurrence of new fires and to ameliorate the forest structure. We studied the effects of thinning and the age of post-fire regeneration (10, 18 and 22 years) on the growth and main reproductive traits of Pinus halepensis trees. Thinning enhanced the growth of trees, the number of reproductive pines and the number of new cones produced per tree. However, thinning also increased the opening of some serotinous cones in the older stands (18 and 22 years). We conclude that thinning in these post-fire regenerated forests should be more strongly recommended to be conducted in younger stands (10 year-old, in our study), because thinning much shortens the non-reproductive period and largely increases the number of new cones produced, in totally serotinous individuals.
Proceedings of the International Workshop, 2005/09/26-30, Bari (Italy)